KARAKTERISTIK GURU DAN SEKOLAH YANG EFEKTIF DALAM PEMBELAJARAN - Arumi Safitri Fatimaningrum (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Instruction is a critical point to reach positive educationaloutcome. Effective instruction based on two aspects: theteachers and school environment. Effective teachers should havethe ability to organize classrooms and manage the student’sbehavior. To achieve that, teacher should enrich those particularaptitude such as class climate arrangement, managementstrategy, feedback and reinforcement policy, and selfimprovement. Providing effective school environment involveinstructional emphasis, evaluation systems, academicexpectation, discipline, also school and class size. The effort toimprove effective instruction should be provided during thepreservice and inservice teacher program.